Asthma in reproductive-aged women with polycystic ovary syndrome and association with obesity. Issue 5 (2nd May 2017) - Htet, Thaw D.; Teede, Helena J.; de Courten, Barbora; Loxton, Deborah; Real, Francisco G.; Moran, Lisa J.; Joham, Anju E.
Recent research suggests that women with polycystic ovary syndrome (PCOS) may have a higher prevalence of asthma. However, there are no epidemiological studies aimed primarily at exploring the relationship between PCOS and asthma, and the effect of body mass index (BMI) on this association. This study is a cross-sectional analyses of data from the Australian Longitudinal Study on Women's Health, a large, community-based, prospective study to examine the association between PCOS and asthma in women aged 28–33 years (n=478 PCOS and n=8134 controls). The prevalence of asthma was 15.2% in women with PCOS and 10.6% in women without PCOS (p=0.004). Women with PCOS who had asthma had a trend for a higher BMI compared with women without asthma (29.9±0.9 versus 27.7±0.4 kg·m −2 ; p=0.054). Women without PCOS who had asthma had a higher BMI compared with women without asthma (26.4±0.2 versus 24.9±0.1 kg·m −2 ; p<0.001). After adjusting for age, BMI and smoking status, PCOS was associated with increased odds of asthma (odds ratio 1.34, 95% CI 1.004–1.79; p=0.047). This study showed both PCOS status and overweight/obese status were independently associated with asthma. Further prospective studies are required to explore the possible mechanisms underpinning the association between asthma and PCOS. In reproductive-aged women, polycystic ovary syndrome is associated with asthma independent of BMI http://ow.ly/YSa330a0vMm